Rekonstruksi Pemikiran Pendidikan Islam: Tela’ah Pemikiran Muhammad Iqbal: Penelitian - Ahmad Husein An Nury; M Satrio Wijaya; Bukhari; Nur Maulida Utari; Muhammad Syaifuddin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This paper examines Muhammad Iqbal's thoughts on Islamic education as a form of conceptual reconstruction of the education system that remains relevant for Muslims in facing the challenges of modernity. As a 20th-century Muslim philosopher and thinker, Iqbal emphasized the importance of holistic education, which integrates intellectual, spiritual, and social dimensions while rejecting the mechanistic and secular nature of colonial education models. At the core of Iqbal's educational philosophy lies the concept of khudi (individuality), which highlights self-development, freedom of thought, and the cultivation of a superior character. Through a library research approach, this study explores Iqbal’s educational principles, including individualism, the balance between physical and spiritual aspects, the role of intellect and intuition, creativity, and social education. The relevance of his ideas lies in their ability to offer a visionary and inclusive framework for Islamic education, aimed at shaping individuals with high integrity who can respond effectively to the dynamics of the times.